BRAND EQUITY TOWARDS REPURCHASING INTENTION OF MOBILE PHONES THROUGH CONSUMER VALUE - Christina Esti Susanti (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
This research is aimed to partially and simultaneously examine the influence of brand equityelement towards repurchasing intention of Nokia cell phones in Surabaya through the customervalue. The populations of this research are the entire Nokia cell phones customers in Surabaya.The numbers of population taken are 150 respondents. The sample was taken by using purposivesampling method. The data are processed and analyzed by using hierarchical regression analysis.The results of the research show that brand equity elements affect the customer value.Consequently, the customer value affects the repurchasing intention of the customers. Inconclusion, the elements of brand equity partially and simultaneously affect the repurchasingintention through the customer value in Surabaya. Based on the results of the research, it issuggested that the producer of Nokia cell phones should creates advertisement in television,which gives the better information about cell phones Nokia specification.Penelitian ini bertujuan menguji pengaruh elemen ekuitas merk terhadap niat membeli ulangmelalui nilai pelanggan baik secara parsial maupun secara simultan pada telepon seluler MerkNokia di Surabaya. Populasi penelitian ini adalah para pengguna telepon seluler merk Nokia diSurabaya. Jumlah sampel dalam penelitian ini ditetapkan sebesar 150 responden. Metodepengambilan sampel menggunakan purposive random sampling. Data diolah dan dianalisisdengan menggunakan hierarchical regression analysis. Hasil penelitian ini menunjukkan bahwaelemen ekuitas merk mempengaruhi nilai pelanggan. Hasil penelitian ini juga membuktikanbahwa nilai pelanggan mempengaruhi niat beli ulang. Kesimpulan yang dapat diambil dalampenelitian ini adalah elemen ekuitas merek baik secara parsial maupun simultan mempengaruhiniat beli ulang melalui nilai pelanggan di Surabaya. Berdasarkan hasil penelitian tersebut, saranbagi produsen telepon seluler adalah merancang iklan di televisi, yang memberikan informasilebih baik tentang spesifikasi telepon seluler merk Nokia.